Exploring COVID-19 vaccine adverse events among pregnant women: a cross-sectional study, 2022 - Ahmed A. Amer; Samar A. Amer; Amerah Badokhon; Sherif M. Hammad; Mohamed A. Wasfy; Misha Khan; Tahani Ateyah Al-Harbi; Sadah Qamous Alobaid; Georgette Eskander; Amro Abdel-Azeem; Abdulmajeed Alshowair; Mohamed Sh. Ramadan (SAGE Publishing, 2024)
Background: Clear and trustworthy information is crucial to improving public acceptance of COVID-19 vaccinations, especially among pregnant women. Given the increased risk of severe viral pneumonia in pregnant women, it is critical to foster confidence in the vaccine's safety and understand any potential adverse events (AEs). So, we did this study in Jeddah, Saudi Arabia (SA), from March to May 2022 to compare women who did not get any doses of the COVID-19 vaccine during pregnancy (Group A) to women who did get at least one dose during pregnancy (Group B) regarding (1) the frequency, types, AEs, and management of its AEs of the COVID-19 vaccination; and (2) exploring pregnancy, delivery, and fetus-related complications (e.g., miscarriage, birth defects, and preterm labor) Methods: A cross-sectional study targeted 438 women who gave birth or were pregnant within the previous 8 weeks. Data was collected through face-to-face interviews with skilled nurses in 13 randomly selected primary healthcare facilities, using a validated, well-structured questionnaire that included the Centers for Disease Control (CDC) COVID-19 vaccination-related AEs. We analyzed the collected data using SPSS version 27. Results: Most participants were aged 25 to less than 35 (58.8%), and 287 (61.3%) were university graduates. There was no statistically significant difference among the studied groups regarding demographics. However, women in Group B had a significantly higher rate of abortions, oligohydramnios (24.4%), abnormal placentas (size and location), 103 (42.7%) abnormal fetal growth, 122 (53.7%) problems breastfeeding, blood pressure problems, and more cases of malaise, headaches, chest pain, breathing problems, and sleep problems than women in Group A. After the second and third doses, the confirmed post-vaccination COVID-19 rates in Group B were lower than those in Group A. Conclusion: The COVID-19 vaccine significantly reduces post-vaccination COVID-19. Although COVID-19 vaccine-related AES are prevalent, analgesics and antipyretics effectively treat most of them.